On nonlinear dynamics in a free fluid surface of a tank excited by a non-ideal power source - Navarro, H. A.; Balthazar, José Manoel [UNESP]; Chavarette, F. R. [UNESP]; Krasnopolskaya, T. S.; Yu. Shvets, A. (ASME International, 2011)
We investigate the nonlinear oscillations in a free surface of a fluid in a cylinder tank excited by non-ideal power source, an electric motor with limited power supply. We study the possibility of parametric resonance in this system, showing that the excitation mechanism can generate chaotic response. Additionally, the dynamics of parametrically excited surface waves in the tank can reveal new characteristics of the system. The fluid-dynamic system is modeled in such way as to obtain a nonlinear differential equation system. Numerical experiments are carried out to find the regions of chaotic solutions. Simulation results are presented as phase-portrait diagrams characterizing the resonant vibrations of free fluid surface and the existence of several types of regular and chaotic attractors. We also describe the energy transfer in the interaction process between the hydrodynamic system and the electric motor. Copyright © 2011 by ASME.
Keywords: Chaotic attractors; Chaotic response; Chaotic solutions; Excitation mechanisms; Free fluids; Free surfaces; Hydrodynamic systems; Interaction process; Limited power supply; Nonlinear differential equation; Nonlinear oscillation; Numerical experiments; Parametric resonance; Parametrically-excited surface waves; Power sources; Resonant vibrations; Differential equations; Dynamical systems; Electric motors; Energy transfer; Exhibitions; Intelligent mechatronics; Mechanical engineering; Surface waves; Tanks (containers)